2022
DOI: 10.1212/cpj.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Tertiary Movement Disorders Subspecialty Care

Abstract: Patient demand continues to outpace growth of the neurology workforce, especially in its subspecialties such as movement disorders. Various strategies have been deployed to address this. The COVID-19 pandemic accentuated the mismatch by propelling telemedicine and access demands to the forefront. Previously, we reported improving general neurology access using a physician-advanced practice provider (APP) team model. Here, we share our experiences of piloting a similar model in subspecialty care (movement disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…New integrated multidisciplinary care models have been emerging to improve quality of care for PwP in the era of the COVID pandemic with its new challenges. An example is a model called the ’physician-advanced practice provider (APP) team model’, recently developed for subspecialty care such as movement disorders in an academic center in the USA [ 62 ]. This model was developed in response to the long waiting times caused by the shortage of neurologists and the growing number of patients waiting to be seen in a movement disorders clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New integrated multidisciplinary care models have been emerging to improve quality of care for PwP in the era of the COVID pandemic with its new challenges. An example is a model called the ’physician-advanced practice provider (APP) team model’, recently developed for subspecialty care such as movement disorders in an academic center in the USA [ 62 ]. This model was developed in response to the long waiting times caused by the shortage of neurologists and the growing number of patients waiting to be seen in a movement disorders clinic.…”
Section: Introductionmentioning
confidence: 99%
“…History taking, physical examination and documentation are performed by the advanced practice providers and residents, while the movement disorders specialist oversees issues related to diagnosis and designs a multidisciplinary individualized management plan for each patient. This model was shown to significantly improve access to subspecialty care for PwP with high patient and team member satisfaction [ 62 ]. A recent review on the efficiency of virtual care for patients with Alzheimer’s disease during the COVID pandemic concluded that successful telemedicine programs are those with the involvement of interdisciplinary teams to manage patient complexity, medical and psychiatric comorbidities, and psychosocial needs with a progressive neurodegenerative condition like Alzheimer’s dementia or Parkinson’s disease [ 63 ].…”
Section: Introductionmentioning
confidence: 99%